Role of Dienogest in the treatment of Endometriosis - Bibi Sajida, Sadaf Ijaz, Shahida Malik, Hani Baloch, Sadia Ijaz, Momenah Maqsood, Monica Punshi (Pakistan Journal of Medical & Health Sciences, 2023)
Endometriosis is a chronic, estrogen-dependent condition affecting women of reproductive age, with peak incidence between 25 and 30 years. Dienogest 2 mg daily has been shown to effectively relieve endometriosis-related pain, reduce endometriotic lesions, and improve quality of life. A quasi-experimental trial at Shifa International Hospital, Islamabad, over 12 months assessed the efficacy of Dienogest 2 mg daily for managing endometriosis-associated pelvic pain (EAPP). The study involved 105 women with a mean age of 28.3 years and a mean BMI of 26.2. EAPP was measured using the Visual Analogue Scale (VAS) at baseline, 3 months, and 6 months. Results indicated a significant reduction in VAS scores from 7.12 at baseline to 4.50 at 3 months and 2.62 at 6 months, demonstrating a clinically meaningful improvement in pain levels. Keywords: Endometriosis, Dienogest, Visual Analogue Score (VAS).